VD_FINDINFO AI 250/10 - 136/2011 vom 10. März 2011 - VD Tribunal cantonal (2011)
PRESTATION D'INVALIDITÉ, RENTE D'INVALIDITÉ, AGGRAVATION DE L'ATTEINTE À LA SANTÉ, ÉVALUATION DE L'INVALIDITÉ | 83 LOJV, 16 LPGA, 17 LPGA, 57 LPGA, 58 LPGA, 8 LPGA, 2 al. 1 let. c LPA-VD, 49 LPA-VD, 52 LPA-VD, 93 al. 1 let. a LPA-VD